STUDY OF FROST RESISTANCE OF CULTIVARS AND LINES OF SOFT WINTER WHEAT - M. M. Ivanisov; E. V. Ionova (Зерновое хозяйство России, 2018)
The method of subjecting plants to frost in the boxes is one of the ways to create provoking conditions for estimating frost tolerance of plants. Frost resistance of winter crops is very dynamic. It increases in the autumn; it is the largest at the beginning and in the middle of the winter and it sharply reduces by the spring. Apart from the seasonal dynamics there is a deviation of frost resistance during the years depending on the conditions of forming frost resistance. We present results of state of the plants after freezing with various temperatures (-18°С; -20°С; -21°С; -22°С). Preservation of varieties and lines after freezing in the boxes changed in dependence of the temperature. The preservation of the plants varied from 32,3 to 88,5 % at -20°С; at -21°С it was 17,2 – 77 % and at -22°С these indexes varied from 0 to 54,5%. The maximum preservation at -22°С has been noted among the cultivars ‘Don 107’ (53,5 %), ‘Donskaya Bezostaya’ (54,5 %) and ‘Asket’ (51,1 %). For more accurate assessment of frost resistance we have used a don method (the method of bushes). The cultivars ‘Donskaya Bezostaya’ (45%), ‘Kapitan’ (43,3 %) and ‘Asket’ (36,7 %) are characterized with a high level of preservation of plants. The productivity of studied samples varied from 5,05 to 7,82 t/ha. The varieties ‘Krasa Dona’ (7,82 t/ha), ‘Ermak (7,74 t/ha) and ‘Lidiya’ (7,45 t/ha) showed the largest productivity. The qualitative traits (protein content, gluten content and SDS-sedimentation) of the studied cultivars and lines have been given in the paper.